The The Role of eco-printing-based occupational therapy in enhancing emotional well-being and quality of life among patients with mental disorders: A Pre-experimental study - Salsabila, Nadia Azzah Aulia; Estria, Suci Ratna (University of Muhammadiyah Malang, 2026)
Introduction: Mental disorders affect thoughts, emotions, and behaviors, often resulting in emotional disturbances and reduced quality of life. Non-pharmacological interventions, including occupational therapy, play an important role in mental health recovery. Eco-printing–based occupational therapy offers a pleasant, stress-free activity that stimulates cognitive, motor, and emotional functions. However, empirical evidence regarding its effectiveness in improving emotional well-being and quality of life remains limited.Objectives: This study aimed to examine the effect of eco-printing–based occupational therapy on emotional well-being and quality of life among patients with mental disorders at the Pondok Lali Jiwa Raga Foundation, Wangon, Banyumas.Methods: A quantitative study with a pre-experimental one-group pretest–posttest design was conducted. A total of 57 participants were recruited using purposive sampling. Emotional status was assessed using the Positive and Negative Affect Schedule (PANAS), and quality of life was measured with the Mental Health Quality of Life (MHQoL) questionnaire. The intervention was implemented over seven days and consisted of ten eco-printing–based occupational therapy sessions. Data were analyzed using the Wilcoxon signed-rank test.Results: Significant differences were observed between pretest and posttest scores. Emotional well-being improved significantly after the intervention (p < 0.001), and quality of life also showed a significant increase (p < 0.001).Conclusions: Eco-printing–based occupational therapy significantly improved emotional well-being and quality of life among patients with mental disorders. These findings indicate that eco-printing may serve as an effective occupational therapy modality in mental health care. However, the absence of a control group and the short intervention duration may limit the generalizability of the results.